Virtual water flow in food trade systems of two West African cities - Akoto-Danso, Edmund K.; Karg, H.; Drechsel, Pay; Nyarko, G.; Buerkert, Andreas (Elsevier, 2019)
Rapid urban growth in sub-Saharan Africa challenges food supply of cities. As food and other organic matter are transported from production areas to consumption points, water, which has been used for their production, is transported virtually. This study aimed at determining the magnitude and sources of virtual water flows in food trade of two West African cities, in order to better assess food provisioning risks and water resource use and planning. To this end, flows of unprocessed food from local, regional, national and international sources were systematically recorded at all roads leading to Tamale, Ghana and Ouagadougou, Burkina Faso. The survey was conducted within two years covering the peak (November - December) and lean season (March - April), respectively, for six days in a row. Virtual water flows were computed by multiplying the flow quantities (t yr-1) by their respective virtual water contents (m3 t-1). Results showed that virtual water of all food commodities imported to Tamale and Ouagadougou were 514 and 2105 million m3 yr-1 respectively, out of which 68% and 40% were re-exported to other regions of the country. The data also showed major seasonal variation in virtual water flows across the year. Reflecting their dominating role in local diets, cereals contributed most to the total virtual water inflows in both cities. Southern Ghana is the major net virtual water importer from Tamale through cereals, legumes, vegetables, and livestock. The Northern Region of Ghana, on the other hand, is a net exporter of virtual water in all food groups apart from fruits. In Ouagadougou, large flows of virtual water were imported in cereals, specifically rice from Asian countries, via Ivory Coast.